IDENTIFICATION OF THE INFLUENCE OF SURFACE URBAN HEAT ISLAND TOWARDS PM 2.5 CONCENTRATION IN DKI JAKARTA - Sabrianti, Indriana
The phenomenon of Surface Urban Heat Island (SUHI) in Jakarta indicates expansion and an increase in temperature intensity. The SUHI effect not only impacts high air temperatures but also significantly contributes to air pollution in Jakarta. Excessive air pollution in cities like PM 2.5 will continue to affect the lives of residents and can pose greater health risks. Therefore, there is a need for a study on the influence of UHI (SUHI) on PM 2.5 concentrations in DKI Jakarta. The data processing of MODIS satellite is conducted to obtain the distribution pattern of Land Surface Temperature (LST) and PM 2.5 concentrations in DKI Jakarta during the period of June, July, August (JJA) from 2011 to 2020. Moderate Resolution Imaging Spectroradiometer (MODIS) is an instrument operating on the Terra satellite. MODIS is the most widely used and popular satellite for surface temperature research. It is also used to estimate Aerosol Optical Depth (AOD) in the study area, which is further processed using the Simplified Aerosol Retrieval Algorithm (SARA) Binning model to estimate PM 2.5 concentrations. The research results show that the average surface temperature of DKI Jakarta during the JJA period from 2011 to 2020 is higher than the surrounding areas in Jabodetabek. The spatial distribution pattern of LST in DKI Jakarta during the JJA period from 2011 to 2020 shows that local heat centers are mainly located in East Jakarta. Areas with high SUHI intensity (Jatinegara, East Jakarta) have lower PM 2.5 concentration values compared to areas with low SUHI intensity (Kebayoran Baru, South Jakarta). The correlation between LST, as well as SUHI intensity, with PM 2.5 concentrations shows a negative correlation at both points -0,56 and -0,43. Areas with high SUHI intensity have relatively low PM 2.5 concentrations, and vice versa.